ANALISIS SISTEM PENGENDALIAN INTERNAL PIUTANG ANGGOTA PADA UNIT USAHA SIMPAN PINJAM - Rantika, Yulia; Syahrudin, Husni; ., Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe study aims to determine the Receivables Internal Control System Members In the Business Unit Primary Savings and Loans Cooperative of West Kalimantan Regional Police. This study is a descriptive evaluative research .. Data analysis in this research using descriptive analysis. In this study, data were collected through the method of documentation and interviews. The results showed that the Internal Control Member Receivables In the Business Unit Primary Savings and Loans Cooperative of West Kalimantan Regional Police are in good enough category, it can be seen from the cooperative's ability to exercise control. From the analysis obtained through interviews with the chairman of the cooperative (board) cooperatives showed that: The procedures and requirements set by the cooperative in accordance with the provision of ART (Bylaws) as set out in the Annual Members Meeting (RAT). That every member who wants to borrow must meet predetermined requirements. This is to prevent unwanted things in the future.Keyword : Internal Control Systems, Accounts Receivable.Â